Cancer genetic counseling communication with low-income Chinese immigrants - Cheng, Janice Ka Yan (J Community Genet, 2017)
As genetics and genomics become part of mainstream medicine, these advances have the potential to either reduce or exacerbate health disparities. Relatively, little research has explored the quality of genetic counseling communication experienced by limited English proficiency patients, especially Chinese Americans. We observed and audio recorded genetic counseling appointments (n = 40) of low-income, limited English-proficient Chinese patients (n = 25) and conducted post-visit interviews (n = 17) using stimulated recall to examine patient understanding of the communication. Standard techniques based in grounded theory, including iterative data review and multiple coders, were used to analyze observation fieldnotes and interview transcripts and to identify these themes: (1) strong beliefs in environmental causes of cancer and skepticism about genetic causes, (2) willingness to undergo genetic testing despite skepticism of hereditary cause of cancer, (3) misunderstanding of key information needed to make informed decisions about testing and screening/prevention options, (4) variable quality of medical interpretation, and (5) selective family communication about cancer and genetic counseling and testing. Together, these themes describe substantial gaps in communication and identify the need for genetic counseling techniques and skills that enable counselors to communicate more effectively across language, literacy, and culture. Understanding the mechanisms of inheritance and the implications of genetic test results can be challenging for anyone, and it is exceptionally daunting for those who have limited English proficiency and/or low literacy. For Chinese immigrant patients to reap the full benefits of genetic counseling and testing, effective communication is essential. Research on interventions to improve communication is needed to ensure that disparities do not widen as genomic medicine reaches a more diverse population.